HOW EXPLORING BODY EXPERIMENTATION IN MODERN THEATER OF WEST SUMATRA: A TWO-DECADE STUDY (1990-2010) PRESENTED? - Saaduddin, Saaduddin; Novalinda, Sherli (Jurusan Sastra Indonesia, 2024)
This article examines the emergence of body experimentation in modern theater groups in West Sumatra from 1990 to 2010, focusing on the motives behind using the body as a communicative medium in theatrical performances. The study aims to comprehend the conceptualization and factors contributing to the presence of innovative theatrical presentations. The literature review explores existing studies on Indonesian theater, particularly modern theater, and relevant works related to West Sumatra theater. Due to limited literature on West Sumatran theater, the study utilizes secondary data from journals, magazines, newspaper clippings, and the internet. The research employs a qualitative methodology, incorporating literature review, observation of selected theater groups engaging in body experimentation, and interviews with key figures. Data analysis involves transcribing interviews, selecting relevant information, categorizing data, and conducting a thorough analysis, revealing the evolution of body experimentation in West Sumatran theater. The discussion section delves into three key themes: the influence of traditional spirit on modern Sumatran theater, body exploration within modern theater groups, and the notable rise of body-centric theater in West Sumatra. The article emphasizes the interconnectedness of these themes and their impact on the dynamic theatrical landscape in the region. In conclusion, the research highlights the significance of body experimentation in West Sumatran modern theater, contributing to a broader understanding of evolving theatrical practices in Indonesia, offering valuable insights for scholars, practitioners, and enthusiasts interested in the dynamic intersection of tradition and innovation in performing arts.